The Relation between Tax Complexity and Foreign Direct Investments: Evidence Across Countries - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren; Voget, Johannes
This paper analyzes the association between tax complexity and foreign direct investments (FDI) based on the newly developed Tax Complexity Index (TCI) and its components. For a sample of 15,607 new foreign subsidiaries, we find no association between total tax complexity, as proxied by the TCI, and the location probability. When we decompose the TCI into tax code complexity and tax framework complexity, we find opposing associations. Tax code complexity is positively related to the location probability, while tax framework complexity is negatively related to it. These associations are, for example, driven by the complexity of transfer pricing and loss offset regulations in the tax code and the dimensions guidance, audits, as well as filing and payments, in the tax framework. In additional analyses, we find that the associations are sensitive to certain characteristics, such as country-specific and firm-specific characteristics. For example, the positive tax code association diminishes when tax rates are high. Overall, we are the first to provide empirical evidence on potential cost-benefit tradeoffs of tax complexity for FDI and thereby enhance prior literature, which has primarily focused on the costs of tax complexity.

Steuerkomplexität als Standortfaktor. So komplex ist das Steuersystem in Deutschland - Sureth-Sloane, Caren (AWV-Informationen)

COVID-19 and investor behavior - Ortmann, Regina; Pelster, Matthias; Wengerek, Sascha Tobias (Finance Research Letters)

Location, location, location: Satellite image-based real-estate appraisal - Kucklick, Jan-Peter; Müller, Oliver (Symposium on Statistical Challenges in Electronic Commerce Research (SCECR))

Care Robot Orientation: What, Who and How? Potential Users` Perceptions - Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Tuisku, Outi; Hennala, Lea; Pekkarinen, Satu; Melkas, Helina; Gustafsson, Christine (International Journal of Social Robotics)

Technologieorientierung zu Assistenzrobotik – Welche Akzeptanz besteht bei der Einführung von Assistenzrobotik für die Pflege älterer Menschen? - Hoppe, Julia Amelie; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Melkas, Helinä; Tusku, Outi; Pekkarinen, Satu; Hennala, Lea (Industrie 4.0 Management)

Assistive robots in care: Expectations and perceptions of older people - Hoppe, Julia Amelie; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Melkas, Helinä; Tusku, Outi; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten (Aging between Participation and Simulation - Ethical Dimensions of Socially Assistive Technologies in elderly care)

Business Model Dependencies: Towards conceptualizing dependencies for extending modeling languages for business models - Vorbohle, Christian; Szopinski, Daniel; Kundisch, Dennis

Share price reactions to tariff imposition announcements in the Trump era - An event study of the trade conflict - Wengerek, Sascha Tobias
Employing a unique sample of 2,849 tariff imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariff announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariff announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariff impositions, e.g. a decrease in the companies' future cash flows and a threat of retaliation. The negative wealth effects are observed irrespective of whether the Trump administration announces safeguard tariffs to protect domestic firms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we find that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariff, trade and firm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariffs; trade conflict

COVID-19 and investor behavior - Ortmann, Regina; Pelster, Matthias; Wengerek, Sascha Tobias (Finance Research Letters)

Terror attacks and individual investor behavior: Evidence from the 2015–2017 European terror attacks - Hasso, Tim; Pelster, Matthias; Breitmayer, Bastian (Journal of Behavioral and Experimental Finance)

Alternative Deals Gain Traction - Sievers, Sönke; Keienburg, Georg; Degen, Dominik; Söllner, Tobias; Kashyrkin, Anton

Downturn M&A: Die Erfolgsstrategie der Stunde? - Sievers, Sönke; Degen, Dominik; Kim, Daniel; Kengelbach, Jens (M&A Review)

Can digital feedback increase employee performance and energy efficiency in firms? Evidence from a field experiment - Hoffmann, Christin; Thommes, Kirsten (Journal of Economic Behavior & Organization)

Decisions on Extending Group Membership—Evidence from a Public Good Experiment - Grund, Christian; Harbring, Christine; Thommes, Kirsten; Tilkes, Katja Rebecca (Games)
We experimentally compare the consequences for group cooperation of two decision mechanisms involving the extension of group membership. We analyze an exogenous decision (random draw) and an endogenous decision (made by a particular group member) mechanism to extend a temporary agent’s group membership. Our results reveal that the prospect of group membership extension affects not only the temporary but also the permanent group members’ contributions with an endogenous mechanism.

Digitale mehrseitige Plattformen – Besser verstehen, wie digitale Plattformen funktionieren - Kundisch, Dennis

Das Technologiedesign umfassend und strukturiert anpassen - Kundisch, Dennis

Förderung von Kompetenzen im Bereich Wirtschat 4.0 an Fachschulen - Kundisch, Dennis

Software tools for business model innovation: Current state and future challenges - Szopinski, Daniel; Schoormann, T.; John, Thomas; Knackstedt, R.; Kundisch, Dennis (Electronic Markets)

Ancillary market signaling: A two-stage model of economic reputation on ancillary market success - Kaimann, Daniel (Applied Economics Letters)

Country-by-Country Reporting Goes Public - Cui Bono? - Lagarden, Martin; Schreiber, Ulrich; Simons, Dirk; Sureth-Sloane, Caren (International Transfer Pricing Journal)
After the introduction of CbCR – pursuant to the BEPS Project (Action 13) in 2015 –, which was established to reduce the information asymmetry between MNEs and tax authorities of the countries they operate in, now public CbCR – as suggested by the EU Commission in 2016 – is discussed as a next step. Here, the objective is to overcome information asymmetries between MNEs and the general public of the countries they operate in. Starting from the assumption that regulators care about the legitimacy of tax laws, this article evaluates pros and cons of public CbCR. The authors find that from the perspective of information asymmetries, public CbCR increases tax transparency only marginally at best. Accordingly, it is concluded that democracies that are based on the rule of law seem to rely on pillories in terms of public CbCR to enforce fair tax payments.

Designing Digital Community Service Platforms for Crowd-Based Services in Urban Areas - Bartelheimer, Christian; Wolf, Verena; Langhorst, Nico; Seegers, Florian (Proceedings of the 15th International Conference on Design Science Research in Information Systems and Technology)

Seven Paradoxes of Business Process Management in a Hyper-Connected World - Beverungen, Daniel; Buijs, Joos C. A. M.; Becker, Jörg; Di Ciccio, Claudio; van der Aalst, Wil M. P.; Bartelheimer, Christian; vom Brocke, Jan; Comuzzi, Marco; Kraume, Karsten; Leopold, Henrik; Matzner, Martin; Mendling, Jan; et al. (Business & Information Systems Engineering)

PS³—A Domain-specific Modeling Language for Platform-based Smart Service Systems - Lüttenberg, Hedda (Designing for Digital Transformation. Co-Creating Services with Citizens and Industry. DESRIST 2020)

What Are We Talking About When We Talk About Technology Pivots? – A Delphi Study - Bohn, Nicolai; Kundisch, Dennis (Information & Management)

The Shanghai-Hong Kong Stock Connect: An Application of the Semi-CGARCH and Semi-EGARCH - Peitz, Christian; Feng, Yuanhua; Gilroy, Bernard Michael; Stöckmann, Nico (Asian Economic and Financial Review)

Die Niedrigzinspolitik der Europäischen Zentralbank - Gilroy, Bernard Michael; Peitz, Christian (WISU – Das Wirtschaftsstudium)

Mechanisms, Preferences, and Heterogeneity in Matching Markets - Stroh-Maraun, Nadja

Technologie Pivots – Warum und wie digitale Startups ihr Technologiedesign umfassend anpassen - Bohn, Nicolai; Kundisch, Dennis (Wirtschaftsinformatik & Management)

Understanding Smart Service Systems Transformation – A Socio-Technical Perspective - Wolf, Verena (Proceedings of the 28th European Conference on Information Systems)

Detecting Workarounds in Business Processes — A Deep Learning Method for Analyzing Event Logs - Weinzierl, Sven; Wolf, Verena; Pauli, Tobias; Beverungen, Daniel; Matzner, Martin (Proceedings of the 28th European Conference on Information Systems)

Reviewing the Simple Things- How Ease of Evaluation Affects Online Rating Behavior - Seutter, Janina; Neumann, Jürgen (Proceedings of the 28th European Conference on Information Systems (ECIS))

Getting Personal with Review Systems – Analyzing the Influence of Personality Traits on the Relationship between Review Templates and Reviewing Behavior - Poniatowski, Martin; Neumann, Jürgen (Proceedings of the 28th European Conference on Information Systems (ECIS))

Distinguishing Knowledge Impact from Citation Impact: A Methodology for Analysing Knowledge Impact for the Literature Review Genre - Schryen, Guido; Wagner, Gerit; Benlian, Alexander
The scientific impact of research papers is multi-dimensional and can be determined quantitatively by means of citation analysis and qualitatively by means of content analysis. Accounting for the widely acknowledged limitations of pure citation analysis, we adopt a knowledge-based perspective on scientific impact to develop a methodology for content-based citation analysis which allows determining how papers have enabled knowledge development in subsequent research (knowledge impact). As knowledge development differs between research genres, we develop a new knowledgebased citation analysis methodology for the genre of standalone literature reviews (LRs). We apply the suggested methodology to the IS business value domain by manually coding 22 LRs and 1,228 citing papers (CPs) and show that the results challenge the assumption that citations indicate knowledge impact. We derive implications for distinguishing knowledge impact from citation impact in the LR genre. Finally, we develop recommendations for authors of LRs, scientific evaluation committees and editorial boards of journals how to apply and benefit from the suggested methodology, and we discuss its efficiency and automatization.
Keywords: Scientific impact; knowledge impact; content-based citation analysis; methodology

The disposition effect in a scopic regime: Data from a laboratory experiment - Liêu, Minh-Lý; Pelster, Matthias (Data in Brief)

Designing a Novel Strategy for Exploring Literature Corpora - Wagner, Gerit; Empl, Philipp; Schryen, Guido (28th European Conference on Information Systems (ECIS 2020))
Understanding a new literature corpus can be a grueling experience for junior scholars. Nevertheless, corresponding guidelines have not been updated for decades. We contend that the traditional strategy of skimming all papers and reading selected papers afterwards needs to be revised. Therefore, we design a new strategy that guides the overall exploratory process by prioritizing influential papers for initial reading, followed by skimming the remaining papers. Consistent with schemata theory, starting with in-depth reading allows readers to acquire more substantial prior content schemata, which are representa-tive for the literature corpus and useful in the following skimming process. To this end, we develop a prototype that identifies the influential papers from a set of PDFs, which is illustrated in a case study in the IT business value domain. With the new strategy, we envision a more efficient process of exploring unknown literature corpora.
Keywords: Reading and skimming; Exploring literature; Review methodology; Design science research; Schemata theory

Data-driven local polynomial for the trend and its derivatives in economic time series - Feng, Yuanhua; Gries, Thomas; Fritz, Marlon (Journal of Nonparametric Statistics)

Modern sector development: The role of exports and institutions in developing countries - Gries, Thomas; Grundmann, Rainer (Review of Development Economics)

Usage of Local Online Platforms in Retail: Insights from retailers' expectations expectations - Berendes, Carsten Ingo; zur Heiden, Philipp; Niemann, Marco; Hoffmeister, Benedikt; Becker, Jörg (Proceedings of the Twenty-Eighth European Conference on Information Systems (ECIS2020))

Design Principles for Explainable Sales Win-Propensity Prediction Systems - Thiess, Tiemo; Müller, Oliver; Tonelli, Lorenzo (International Conference on Wirtschaftsinformatik)

The gambler’s and hot-hand fallacies: Empirical evidence from trading data - Pelster, Matthias (Economics Letters)

Integrating Management Science into the HPC Research Ecosystem - Schryen, Guido (Communications of the ACM)

Capabilities for Ambidextrous Innovation of Digital Service - Wolf, Verena; Lüttenberg, Hedda (Proceedings of the 15th International Conference on Wirtschaftsinformatik)

Establishing Smart Service Systems is a Challenge: A Case Study on Pitfalls and Implications - Wolf, Verena; Franke, Alena; Bartelheimer, Christian; Beverungen, Daniel (Proceedings of the 15th International Conference on Wirtschaftsinformatik)

Interview with Utz-Uwe Haus on “High Performance Computing in Economic Environments: Opportunities and Challenges" - Schryen, Guido; Kliewer, Natalia; Fink, Andreas (Business & Information Systems Engineering)
This interview is part of the special issue (01/2020) on “High Performance Business Computing” to be published in the journal Business & Information Systems Engineering. The interviewee Utz-Uwe Haus is Senior Research Engineer @ CRAY European Research Lab (CERL)). A bio of him is included at the end of the interview.

Arbeitsrechtliche Rechtsprechung des EuGH im Jahre 2019 - Krimphove, Dieter (ArbR – Arbeitsrecht Aktuell)

Framing and the disposition effect in a scopic regime - Liêu, Minh Ly; Pelster, Matthias (The Quarterly Review of Economics and Finance)

Essays on the Theory of Industrial Organization: Credence Goods, Vertical Relations and Product Bundling - Heinzel, Joachim

Parallel computational optimization in operations research: A new integrative framework, literature review and research directions - Schryen, Guido (European Journal of Operational Research)

Nudging in Judging- Differences in Online Rating Behavior for Utilitarian and Hedonic Service Aspects - Seutter, Janina; Neumann, Jürgen; Kundisch, Dennis (Tagungsband der 15. Internationalen Tagung Wirtschaftsinformatik 2020 (WI))

Visualize different: Towards researching the fit between taxonomy visualizations and taxonomy tasks - Szopinski, Daniel; Schoormann, Thorsten; Kundisch, Dennis (Tagungsband der 15. Internationalen Tagung Wirtschaftsinformatik 2020 (WI))

You Write What You Are - Exploring the Relationship between Online Reviewers' Personality Traits and Their Reviewing Behavior - Poniatowski, Martin; Neumann, Jürgen (Tagungsband der 15. Internationalen Tagung Wirtschaftsinformatik 2020 (WI))

Die „Logik“ der Überzeugungskraft - Krimphove, Dieter (Rechtstheorie)

How to Build Trust on Peer-to-Peer Platforms: An Investigation of the Antecedents of Peer and Platform Trust - Purrmann, Maren; Wünderlich, Nancy (Proceedings of the 2020 AMA Winter Academic Conference)

Timing in Information Security: An Event Study on the Impact of Information Security Investment Announcements - Szubartowicz, Eva; Schryen, Guido (Journal of Information System Security)
Timing plays a crucial role in the context of information security investments. We regard timing in two dimensions, namely the time of announcement in relation to the time of investment and the time of announcement in relation to the time of a fundamental security incident. The financial value of information security investments is assessed by examining the relationship between the investment announcements and their stock market reaction focusing on the two time dimensions. Using an event study methodology, we found that both dimensions influence the stock market return of the investing organization. Our results indicate that (1) after fundamental security incidents in a given industry, the stock price will react more positively to a firm’s announcement of actual information security investments than to announcements of the intention to invest; (2) the stock price will react more positively to a firm’s announcements of the intention to invest after the fundamental security incident compared to before; and (3) the stock price will react more positively to a firm’s announcements of actual information security investments after the fundamental security incident compared to before. Overall, the lowest abnormal return can be expected when the intention to invest is announced before a fundamental information security incident and the highest return when actual investing after a fundamental information security incident in the respective industry.
Keywords: Event Study; Information Security; Investment Announcements; Stock Price Reaction; Value of Information Security Investments

Gender, competitiveness, and task difficulty: Evidence from the field - Hoyer, Britta; van Huizen, Thomas; Keijzer, Linda; Rezaei, Sarah; Rosenkranz, Stephanie; Westbrock, Bastian (Labour Economics)
This study examines the gender gap in competitiveness in an educational setting and tests whether this gap depends on the difficulty of the task at hand. For this purpose, we administered a series of experiments during the final exam of a university course. We confronted three cohorts of undergraduate students with a set of bonus questions and the choice between an absolute and a tournament grading scheme for these questions. To test the moderating impact of task difficulty, we (randomly) varied the difficulty of the questions between treatment groups. We find that, on average, women are significantly less likely to select the tournament scheme. However, the results show that the gender gap in tournament entry is sizable when the questions are relative easy, but much smaller and statistical insignificant when the questions are difficult.

Designing City Center Area Recommendation Systems - zur Heiden, Philipp; Berendes, Carsten Ingo; Beverungen, Daniel (Proceedings of the 15th International Conference on Wirtschaftsinformatik)
To decide in which part of town to open stores, high street retailers consult statistical data on customers and cities, but they cannot analyze their customers’ shopping behavior and geospatial features of a city due to missing data. While previous research has proposed recommendation systems and decision aids that address this type of decision problem – including factory location and assortment planning – there currently is no design knowledge available to prescribe the design of city center area recommendation systems (CCARS). We set out to design a software prototype considering local customers’ shopping interests and geospatial data on their shopping trips for retail site selection. With real data on 500 customers and 1,100 shopping trips, we demonstrate and evaluate our IT artifact. Our results illustrate how retailers and public town center managers can use CCARS for spatial location selection, growing retailers’ profits and a city center’s attractiveness for its citizens.
Keywords: Town Center Management; High Street Retail; Recommender Systems; Geospatial Recommendations; Design Science Research

Transformation of Actors’ Roles in Service Systems: A Multi-Level Analysis - Wolf, Verena; Bartelheimer, Christian (16th International Research Conference in Service Management)

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja (Games and Economic Behavior)
We analyze the actual behavior of agents in a matching mechanism, using data from a clearinghouse at the Faculty of Business Administration and Economics at a German university, where a variant of the Boston mechanism is used. We supplement this data with data generated in a survey among the students who participated in the clearinghouse. We find that under the current mechanism over 74% of students act strategically by misrepresenting at least one of their preferences. Nevertheless, not all students are able to improve their outcome by doing so. We show that this is mainly due to the incomplete information of students and naiveté. Sophisticated students actually reach significantly better outcomes than naive students. Thus, we find evidence that naive students are exploited by sophisticated students in an incomplete information setting.

Criteria as a prelude for guiding taxonomy evaluation - Szopinski, Daniel; Schoormann, Thorsten; Kundisch, Dennis (Proceedings of the 53rd Hawaii International Conference on System Sciences (HICSS))

Determinants of nursing home choice: Does reported quality matter? - Schmitz, Hendrik; Stroka‐Wetsch, Magdalena A. (Health Economics)
Keywords: Health Policy

Trust development in care robots by opinion leader in the society - Thommes, Kirsten; Johansson-Pajala, Rose-Marie; Gustaffson, Christine; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Melkas, Helinä; Hoppe, Julia Amelie (Gerontechnology)

The fast and the furious—An experimental investigation of the pace of life and risky speed choice in traffic - Goldbach, Carina; Hoffmann, Christin; Hoppe, Julia Amelie; Pitz, Thomas; Thommes, Kirsten (PloS ONE)

Embedding care robots into society and practice: Socio-technical considerations - Pekkarinen, Satu; Hennala, Lea; Tuisku, Outi; Gustafsson, Christine; Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Melkas, Helina (Futures)

Early Disclosure of Invention and Reduced Duplication: An Empirical Test - Lück, Sonja; Balsmeier, Benjamin; Seliger, Florian; Fleming, Lee (Management Science)
Much work on innovation strategy assumes or theorizes that competition in innovation elicits duplication of research and that disclosure decreases such duplication. We validate this empirically using the American Inventors Protection Act (AIPA), three complementary identification strategies, and a new measure of blocked future patent applications. We show that AIPA—intended to reduce duplication, through default disclosure of patent applications 18 months after filing—reduced duplication in the U.S. and European patent systems. The blocking measure provides a clear and micro measure of technological competition that can be aggregated to facilitate the empirical investigation of innovation, firm strategy, and the positive and negative externalities of patenting. This paper was accepted by Joshua Gans, business strategy.
Keywords: Management Science and Operations Research; Strategy and Management

A Knowledge Development Perspective on Literature Reviews: Validation of a New Typology in the IS Field - Schryen, Guido; Wagner, Gerit; Benlian, Alexander; Paré, Guy (Communications of the AIS)
Literature reviews (LRs) play an important role in the development of domain knowledge in all fields. Yet, we observe a lack of insights into the activities with which LRs actually develop knowledge. To address this important gap, we (1) derive knowledge building activities from the extant literature on LRs, (2) suggest a knowledge-based typology of LRs that complements existing typologies, and (3) apply the suggested typology in an empirical study that explores how LRs with different goals and methodologies have contributed to knowledge development. The analysis of 240 LRs published in 40 renowned IS journals between 2000 and 2014 allows us to draw a detailed picture of knowledge development achieved by one of the most important genres in the IS field. An overarching contribution of our work is to unify extant conceptualizations of LRs by clarifying and illustrating how LRs apply different methodologies in a range of knowledge building activities to achieve their goals with respect to theory.
Keywords: Literature review; knowledge development; knowledge building activities; knowledge-based typology; information systems research

High Performance Business Computing - Schryen, Guido; Kliewer, Natalia; Fink, Andreas (Business & Information Systems Engineering)

Introduction to the Special Issue “Bargaining” - Haake, Claus-Jochen; Trockel, Walter (Homo Oeconomicus)
Keywords: Industrial and Manufacturing Engineering; Environmental Engineering

A Case for a New IT Ecosystem: On-The-Fly Computing - Karl, Holger; Kundisch, Dennis; Meyer auf der Heide, Friedhelm; Wehrheim, Heike (Business & Information Systems Engineering)

Location Choice and Quality Competition in Mixed Hospital Markets - Hehenkamp, Burkhard; Kaarbøe, Odvar M. (Journal of Economic Behavior & Organization)
Many countries have opened their health care markets to private for-profit providers, aiming to promote quality and choice for patients. The prices are regulated and providers compete in location and quality. We show that whereas opening a public hospital market typically raises quality, the private provider strategically locates towards the corner of the market to avoid costly quality competition. Social welfare depends on the size of the regulator's budget and on the altruism of the public provider. If the budget is large, high quality results and welfare is highest in a duopoly whenever entry is optimal. If the budget is small, quality levels in a duopoly mirror the quality level in a monopoly. It can be optimal for the regulator not to use the full budget.

Business Intelligence & Analytics Cost Accounting: An Action Design Research Approach - Grytz, Raphael; Krohn-Grimberghe, Artus; Müller, Oliver (European Conference on Information Systems)
In order to sustain their competitive advantage, data driven organizations must continue investing in business intelligence and analytics (BI&A) while mitigating inherent cost increases. Research shows that examining outlays by individual BI&A artifact (e.g. reports, analytics) is necessary, but introduction in practice is cumbersome and adoption is slow. BI&A service-oriented cost allocation (BIASOCA) represents an improvement to this situation. This approach enables to render the BI&A cost pool accountable and improves cost transparency, which leads to a higher BI&A penetration of economically viable applications in organizations. Against this background, this paper aims at designing and implementing BIASOCA in a medium-sized company. To record organizational impact and increase customer acceptance, this study is carried out as action design research (ADR). Our findings indicate improvements in BI&A management from working with consumers to locate cost savings and drivers. After invoicing, consumers’ BI&A awareness increased, releasing resources while also making a better understanding of BIASOCA necessary. We detail how to implement BIASOCA in a real-life setting and the challenges attendant in so doing. Our research contributes to theory and practice with a set of design principles highlighting, besides the accuracy of cost accounting, the importance of collaboration, model comprehensibility and strategic alignment.

Trade and economic development: global causality and development- and openness-related heterogeneity - Gries, Thomas; Redlin, Margarete (International Economics and Economic Policy)

Forecasting IT Security Vulnerabilities - An Empirical Analysis - Yasasin, Emrah; Prester, Julian; Wagner, Gerit; Schryen, Guido (Computers & Security)
Today, organizations must deal with a plethora of IT security threats and to ensure smooth and uninterrupted business operations, firms are challenged to predict the volume of IT security vulnerabilities and allocate resources for fixing them. This challenge requires decision makers to assess which system or software packages are prone to vulnerabilities, how many post-release vulnerabilities can be expected to occur during a certain period of time, and what impact exploits might have. Substantial research has been dedicated to techniques that analyze source code and detect security vulnerabilities. However, only limited research has focused on forecasting security vulnerabilities that are detected and reported after the release of software. To address this shortcoming, we apply established methodologies which are capable of forecasting events exhibiting specific time series characteristics of security vulnerabilities, i.e., rareness of occurrence, volatility, non-stationarity, and seasonality. Based on a dataset taken from the National Vulnerability Database (NVD), we use the Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) to measure the forecasting accuracy of single, double, and triple exponential smoothing methodologies, Croston's methodology, ARIMA, and a neural network-based approach. We analyze the impact of the applied forecasting methodology on the prediction accuracy with regard to its robustness along the dimensions of the examined system and software package "operating systems", "browsers" and "office solutions" and the applied metrics. To the best of our knowledge, this study is the first to analyze the effect of forecasting methodologies and to apply metrics that are suitable in this context. Our results show that the optimal forecasting methodology depends on the software or system package, as some methodologies perform poorly in the context of IT security vulnerabilities, that absolute metrics can cover the actual prediction error precisely, and that the prediction accuracy is robust within the two applied forecasting-error metrics.

Integration of Novel Sensors and Machine Learning for Predictive Maintenance in Medium Voltage Switchgear to Enable the Energy and Mobility Revolutions - Hoffmann, Martin W.; Wildermuth, Stephan; Gitzel, Ralf; Boyaci, Aydin; Gebhardt, Jörg; Kaul, Holger; Amihai, Ido; Forg, Bodo; Suriyah, Michael; Leibfried, Thomas; Stich, Volker; Hicking, Jan; et al. (Sensors)
The development of renewable energies and smart mobility has profoundly impacted the future of the distribution grid. An increasing bidirectional energy flow stresses the assets of the distribution grid, especially medium voltage switchgear. This calls for improved maintenance strategies to prevent critical failures. Predictive maintenance, a maintenance strategy relying on current condition data of assets, serves as a guideline. Novel sensors covering thermal, mechanical, and partial discharge aspects of switchgear, enable continuous condition monitoring of some of the most critical assets of the distribution grid. Combined with machine learning algorithms, the demands put on the distribution grid by the energy and mobility revolutions can be handled. In this paper, we review the current state-of-the-art of all aspects of condition monitoring for medium voltage switchgear. Furthermore, we present an approach to develop a predictive maintenance system based on novel sensors and machine learning. We show how the existing medium voltage grid infrastructure can adapt these new needs on an economic scale.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Inszenierungen im digitalen Bild. Eine Rekonstruktion der Selfie-Praktiken Jugendlicher mittels der Dokumentarischen Bildinterpretation. - Schwabl, Franziska

Fotografien als Zugang zur Lebenswelt Jugendlicher. Eine Analyse der digitalen Inszenierungspraktiken Jugendlicher im berufsschulischen Übergangssystem. - Schwabl, Franziska (bwp@Berufs-und Wirtschaftspädagogik – online)

Against All Odds: Tentative Steps Toward Efficient Information Sharing in Groups - Schlangenotto, Darius; Schnedler, Wendelin; Vadovic, Radovan (Games)

Revisiting a Remedy Against Chains of Unkindness - Schnedler, Wendelin; Stephan, Nina Lucia (Schmalenbach Business Review)

Extending Loyalty Programs with BI Functionalities A Case Study for Brick-and-Mortar Stores - Kucklick, Jan-Peter; Kamm, Michael Reiner; Schneider, Johannes; vom Brocke, Jan (Proceedings of the 53rd Hawaii International Conference on System Sciences)
Effective customer loyalty programs are essential for every company. Small and medium sized brick-and- mortar stores, such as bakeries, butcher and flower shops, often share a common overarching loyalty program, organized by a third-party provider. Furthermore, these small shops have limited resources and often cannot afford complex BI tools. Out of these reasons we investigated how traditional brick-and- mortar stores can benefit from an expansion of service functionalities of a loyalty card provider. To answer this question, we cooperated with a cross-industry customer loyalty program in a polycentric region. The loyalty program was transformed from simple card-based solution to a mobile app for customers and a web- application for shop owners. The new solution offers additional BI services for performing data analytics and strengthening the position of brick-and-mortar stores. Participating shops can work together in order to increase sales and align marketing campaigns. Therefore, shopping data from 12 years, 55 shops, and 19,000 customers was analyzed.
Keywords: brick-and-mortar stores; business intelligence; case study; loyalty program

Data mining for small shops: Empowering brick-and-mortar stores through BI functionalities of a loyalty program1 - Kamm, Michael Reiner; Kucklick, Jan-Peter; Schneider, Johannes; vom Brocke, Jan (Information Systems Management)
While the analysis and usage of data are increasing in importance, the application of sophisticated BI solutions in small stores is limited by available technical capabilities and financial resources. This study investigates how brick-and-mortar stores can benefit from an expansion of service functionalities of a cross-industry loyalty card provider. Digitalizing the loyalty program created new opportunities, while the analysis of shopping data of 13 years, 19,000 customers, and 55 shops empowered data-based decision support.
Keywords: Customer loyalty; case study; brick-and-mortar stores; business intelligence; loyalty programs

Information Design in Coordination Games with Risk Dominant Equilibrium Selection - Ebert, Michael; Kadane, Joseph (Jay) B.; Simons, Dirk; Stecher, Jack Douglas

Kapazitätsplanung im Rahmen eines strategischen Kooperationsmanagements - Betz, Stefan (Neuere Entwicklungen in Produktion und Controlling)

Zieloptimale Anzahl von Partnern in Beschaffungskollaborationen - Osthoff, Lennart (Neuere Entwicklungen in Produktion und Controlling)

Zieloptimale Variantenvielfalt in der Produktionsplanung - Betz, Stefan (Neuere Entwicklungen in Produktion und Controlling)

Neuere Entwicklungen in Produktion und Controlling

Produktionsprogrammplanung bei variierender Fertigungstiefe - Plückebaum, Daniel (Neuere Entwicklungen in Produktion und Controlling)

Eignung ausgewählter Entscheidungsunterstützungsinstrumente für die Planung, Steuerung und Kontrolle von Produktinnovationen - Heidmann , Mathis (Neuere Entwicklungen in Produktion und Controlling)

Kollaborationsentscheidungen im Supply Chain Management - Osthoff, Lennart

Marktmissbrauch in digitalen Märkten - eine wettbewerbspolitische Analyse mit Fallbeispielen von Google, Facebook und Amazon - Niggemeyer, Laura

Challenges for Competition Policy in Data-Driven Mergers - Schlegel, Manuela

Marktmissbrauch in digitalen Märkten - Eine wettbewerbspolitische Analyse am Beispiel von Facebook - Neibert, Katharina

Zu den volkswirtschaftlichen Auswirkungen von Marktmacht am Fallbeispiel der Walt Disney Company - Naseri, Gitti

Preisdifferenzierung im Online-Handel am Beispiel Amazon und Obi - Laudage, Felix

Zuordnung und Anreizkompatibilität - Eine experimentelle Untersuchung - Posmetni, Lena

Auswirkungen der Preisdiskriminierung im Online Handel - Eine Wohlfahrtsanalyse am Beispiel von Amazon - Hensel, Jason

Zur Effizienzsteigerung durch Reputationsmechanismen auf digitalen Märkten - Multani, Manjinder Singh

Information asymmetry and the SEC framework in digital markets - On the role of reputation systems in alleviating buyers' skepticism and inducing their willingness to pay - Bellouchi, Houda

Auswirkungen der digitalen Flexibilisierung des Fertigungsortes auf die Verteilung der Besteuerungsrechte – Ergebnisse von Modellrechnungen zum 3D-Druck-Verfahren - Mair, Christina; Scheffler, Wolfram; Senger, Isabell; Sureth-Sloane, Caren (Steuer und Wirtschaft)

COVID-19 and investor behavior - Ortmann, Regina; Pelster, Matthias; Wengerek, Sascha Tobias (Finance Research Letters)
Keywords: Finance

Zuordnungsverfahren für Tauschbörsen - N., N.